Edukasi Penerapan Finger Hold Dan Classical Music Therapy Mozart Dalam Menurunkan Skala Nyeri Pada Pasien Post Operasi Laparatomi Di RS Dr. M. Djamil Padang - Weny Amelia; Ria Desnita; Lola Despitasari; Fitria Alisa; Lenni Sastra; Zulham Efendi (JURNAL ABDI MERCUSUAR, 2025)
Background: Post-laparotomy patients commonly experience acute pain due to the extent and depth of the surgical incision, which can interfere with comfort, mobility, and the recovery process. Pain management is still dominated by pharmacological approaches, while the utilization of nursing-based non-pharmacological interventions is not optimal. This community service activity aims to reduce the pain scale of post-laparotomy patients through education on the combination of finger-hold relaxation techniques and Mozart classical music therapy as a safe and easy-to-apply non-pharmacological intervention. Methods: The community service activity was implemented using an educational-participatory approach through education, demonstrations, and direct assistance to 10 post-laparotomy patients and their families in the Operating Room of Dr. M. Djamil Padang Hospital on October 2, 2025. Evaluation was conducted by measuring the pain scale using the Numeric Rating Scale (NRS) before and after the intervention, as well as observing the patients' ability to apply therapy independently. Results: Before the intervention, 60% of patients were in the severe pain category (scale 7–10) and 40% were in the moderate pain category (scale 4–6). After the intervention, 70% of patients experienced mild pain (scale 1–3) and 30% experienced moderate pain (scale 4–6), with no further patients experiencing severe pain. Furthermore, 100% of patients were able to independently apply the finger hold technique and Mozart classical music therapy as part of post-laparotomy pain management.